Talent identification and development in youth sports: A systematic review - Shahidi, S. H.; Carlberg, B.; Kingsley, J. D. (International Journal of Kinanthropometry, 2023)
Introduction: Talent has traditionally been associated with the concept of an athlete's essential conditions for success. Longitudinal studies can assess characteristics associated with performance while evaluating changes and developments over time. Therefore, the goal of this review was to identify and summarize the longitudinal literature that addresses the impact of the development of potential talent indicators in childhood/adolescence on later success in elite sports.